Proceedings of the 4th International Conference on Mobile and Ubiquitous Multimedia - MUM '05 2005
DOI: 10.1145/1149488.1149504
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone based AR scene assembly

Abstract: In this paper we describe a mobile phone based Augmented Reality application for 3D scene assembly. Augmented Reality on mobile phones extends the interaction capabilities on such handheld devices. It adds a 6 DOF isomorphic interaction technique for manipulating 3D content. We give details of an application that we believe to be the first where 3D content can be manipulated using both the movement of a camera tracked mobile phone and a traditional button interface as input for transformations. By centering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…There are a large variety of application fields where services can be pervasively accessed by mobile devices, such as context-aware information provision within university campuses (Genco et al, 2005), interactive user profile-based guides in cultural heritage sites (Pilato et al, 2006;Raptis et al, 2005;Andolina et al, 2012), augmented reality objects assembly in mobility (Henrysson et al, 2005) and healthcare systems (Price and Summers, 2006;Vuong et al, 2009).…”
Section: Smartphones As Unique Interaction Devices?mentioning
confidence: 99%
“…There are a large variety of application fields where services can be pervasively accessed by mobile devices, such as context-aware information provision within university campuses (Genco et al, 2005), interactive user profile-based guides in cultural heritage sites (Pilato et al, 2006;Raptis et al, 2005;Andolina et al, 2012), augmented reality objects assembly in mobility (Henrysson et al, 2005) and healthcare systems (Price and Summers, 2006;Vuong et al, 2009).…”
Section: Smartphones As Unique Interaction Devices?mentioning
confidence: 99%
“…The results of these studies showed that AR has great potential as a way to give instructions on how to perform more or less complicated tasks in the health care domain. Other researchers have illustrated the use of AR in process industry and object assembly [34], training and education [7], mobile phones [13], mobile applications [29] etc.…”
Section: Collaborative Augmented Realitymentioning
confidence: 99%
“…The results of these studies showed that AR has great potential as a way to give instructions on how to perform more or less complicated tasks in the health care domain. Other researchers have illustrated the use of AR in process industry and object assembly [28], training and education [6], mobile phones [14], mobile applications [25] etc.…”
Section: Collaborative Augmented Realitymentioning
confidence: 99%